Thank You to Our 2017 Peer Reviewers. Issue 9 (19th September 2018) - Brewer, Peter; Chambers, Don; Hetland, Robert; Karnauskas, Kristopher; Lowe, Ryan; Moran, S. Bradley; Oey, Lie‐Yauw; Pinardi, Nadia; Proshutinsky, Andrey
Abstract: Similar to the construction of physical ships and laboratory buildings, scientific knowledge is built incrementally and requires solid components of data, theory, and methodology at each phase of the "construction." The peer‐review process provides the necessary "inspection" and the assurance that every step of the construction is solid, particularly in regard to the proper use of the scientific method. The peer‐review process helps improve the published work by providing constructive suggestions and by safeguarding against scientific work that could later be found to be built on shaky foundations. Because no single scientist has intimate knowledge of today's many aspects of the Ocean Sciences, we rely on each other's expertise to serve as unbiased "inspectors" of published articles. Your considerable time and effort, spent reviewing JGR‐Oceans manuscript(s) during 2017, are sincerely appreciated by our editorial board and by the Ocean Science community at large. We thank you for rising to this professional challenge and for your wisdom, commitment, skill, and service. Plain Language Summary: Similar to the construction of physical ships and laboratory buildings, scientific knowledge is built incrementally and requires solid components of data, theory, and methodology at each phase of the "construction". The peer review process provides the necessary "inspection" and the assurance that every step of the construction is solid, particularly in regard to the proper use of the scientific method. The peer‐review process helps improve the published work by providing constructive suggestions, and by safe‐guarding against scientific work that could later found to be built on shaky foundations. Because no single scientist has intimate knowledge of today's many aspects of the Ocean Sciences, we rely on each other's expertise to serve as unbiased "inspectors" of published articles. Your considerable time and effort, spent reviewing JGR‐Oceans manuscript(s) during 2017, are sincerely appreciated by our editorial board, and by the Ocean Science community at large. We thank you for rising to this professional challenge, and for your wisdom, commitment, skill, and service. Key Point: The JGR‐Oceans Editors thank all the peer reviewers from 2017